2023
DOI: 10.3390/jmse11061163
|View full text |Cite
|
Sign up to set email alerts
|

Improving Significant Wave Height Prediction Using a Neuro-Fuzzy Approach and Marine Predators Algorithm

Abstract: This study investigates the ability of a new hybrid neuro-fuzzy model by combining the neuro-fuzzy (ANFIS) approach with the marine predators’ algorithm (MPA) in predicting short-term (from 1 h ahead to 1 day ahead) significant wave heights. Data from two stations, Cairns and Palm Beach buoy, were used in assessing the considered methods. The ANFIS-MPA was compared with two other hybrid methods, ANFIS with genetic algorithm (ANFIS-GA) and ANFIS with particle swarm optimization (ANFIS-PSO), in predicting signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In comparison to the initial ECMWF SWH projections, the spring correction proved to be the most successful, with a mean absolute error reduction of 12.972-46.237%. Ikram and Cao [24] investigated the performance of a unique hybrid neuro-fuzzy model for the short-term (one hour to one day) prediction of SWH. This model combines the Adaptive-Network-based Fuzzy Inference System (ANFIS) method with the Marine Predator Algorithm (MPA), improving the accuracy of ANFIS-PSO and ANFIS-GA by 8.30% and 11.20%, respectively, in terms of root mean square errors during the prediction of a 1 h lead time in the test period.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the initial ECMWF SWH projections, the spring correction proved to be the most successful, with a mean absolute error reduction of 12.972-46.237%. Ikram and Cao [24] investigated the performance of a unique hybrid neuro-fuzzy model for the short-term (one hour to one day) prediction of SWH. This model combines the Adaptive-Network-based Fuzzy Inference System (ANFIS) method with the Marine Predator Algorithm (MPA), improving the accuracy of ANFIS-PSO and ANFIS-GA by 8.30% and 11.20%, respectively, in terms of root mean square errors during the prediction of a 1 h lead time in the test period.…”
Section: Introductionmentioning
confidence: 99%
“…In a relevant study, Pourzangbar et al [13] demonstrated that the prediction of scour depth due to non-breaking waves with the aid of Machine Learning (ML) models such as regression trees and support vector regression achieves the highest accuracy. Therefore, soft computing and ML methods, which fall under artificial intelligence methodologies, have been successfully utilized in modeling wave characteristics and wave heights [14][15][16]. Besides the beneficial features of the ML methodologies, it should be mentioned that the majority of ML models do not offer a simple, explicit description of the mathematical structure of the constructed models.…”
Section: Introductionmentioning
confidence: 99%
“…The MPA-CNN included a combination of heavy feature extraction and classification techniques. Ikram et al [22] proposed a hybrid model with the ANFIS and MPA to estimate short-term significant wave heights. The results were compared with two different models, the ANFIS with the GA (ANFIS-GA) and the ANFIS with PSO (ANFIS-PSO).…”
Section: Introductionmentioning
confidence: 99%